Brexit: A Hard-but-Smart Strategy and Its Consequences - Gabriel J. Felbermayr (Intereconomics, 2019)
Would the United Kingdom really apply high EU external tariffs in the case of a hard Brexit and carry out extensive physical checks at their border? Recent developments in London call this into question. A hard-but-smart strategy would fundamentally change Britain's position vis-à-vis the EU and potentially result in a constructive alternative.
Keywords: 330